2013
DOI: 10.1039/c3dt51149a
|View full text |Cite
|
Sign up to set email alerts
|

Current density enhancement in ZnO/CdSe photoelectrochemical cells in the presence of a charge separating SnO2 nanoparticles interfacing-layer

Abstract: Photoelectrochemical cells (PECs) of ZnO/CdSe decorated with a charge separating SnO2 nanoparticles (NPs) layer of various thicknesses are prepared and characterized by using scanning electron microscopy (SEM), electrochemical impedance spectroscopy (EIS), UV-visible absorption, energy dispersive X-ray analysis spectroscopy (EDX) and incident photon-to-current conversion efficiency (IPCE) measurements. A uniform coverage of the SnO2 NPs layer over ZnO/CdSe electrode surface is evidenced. The EDX elemental mapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The important advantage of photonic sintering is that it eliminates the need for heating at high temperature, which not only reduces the fabrication time, but also allows the use of inexpensive plastic substrates applicable in exible electronics. [62][63][64][65] In order to show that our photonic-sintered ZnO NSs led to the improved charge transfer characteristics of the dye cell, we conducted electrochemical impedance spectroscopy (EIS) measurements. The equivalent circuit used for the EIS measurements and the extracted EIS electronic parameters are presented in the ESI in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The important advantage of photonic sintering is that it eliminates the need for heating at high temperature, which not only reduces the fabrication time, but also allows the use of inexpensive plastic substrates applicable in exible electronics. [62][63][64][65] In order to show that our photonic-sintered ZnO NSs led to the improved charge transfer characteristics of the dye cell, we conducted electrochemical impedance spectroscopy (EIS) measurements. The equivalent circuit used for the EIS measurements and the extracted EIS electronic parameters are presented in the ESI in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Considering these limitations of the conventional sintering process, the development of a novel sintering technique that is suitable for all types of solar cells is highly desired but it is still challenging to achieve a better PCE swily and efficiently without damaging the nanostructures and heat-sensitive substrates. 24 In recent years, several researchers have demonstrated that ash white light (FWL), [25][26][27][28][29][30] UV irradiation, 31 microwave irradiation, 32 laser sintering [33][34][35] and IR sintering 36 can be used for sintering a metal oxide and Cu-nanolinks and for the fabrication of TiO 2 as well as for counter electrode development. Among these, FWL-based sintering is essentially a sintering technique, which, in contrast to conventional oven sintering, employs the heat generated locally by the absorption of visible light in the target material to achieve the necessary temperature for sintering the material.…”
Section: Introductionmentioning
confidence: 99%
“…DSSCs were fabricated to evaluate the CE performance of the MoTe 2 films using our method 38 41 . Briefly, thin blocking layer TiO 2 was deposited onto a cleaned FTO glass substrate (15 × 15 mm 2 ) by dipping it in 40 mM TiCl 4 solution for 30 min at 70 °C and annealing it at 450 °C for 30 min.…”
Section: Discussionmentioning
confidence: 99%
“…Layer of SnO 2 nanoparticles over the ZnO/CdS photoanode enhances electron transportation and suppress charge recombination resulting into 55% increased PCE limited to 3.41% compared to bare ZNO/CdS based solar cell [99].…”
Section: Morphological Effectmentioning
confidence: 99%